Evaluasi Penambahan Tepung Moluska Bakau (Telescopium telescopium) pada Pakan Komersil terhadap Kinerja Petumbuhan Benih Ikan Patin (Pangasius sp.) - Safrun, Muhammad; Komariyah, Siti; Rosmaiti, Rosmaiti (Universitas Gajah Putih, 2022)
This study aims to analyze the effect of adding mangrove mollusk flour to the growth of catfish. The hope is that mangrove mollusk flour can replace fish meal and soybean meal as a source of protein in feed. The design used in this study was a completely randomized design with 5 treatments and 3 replications. The treatments in this study were P1 (control), P2 (commercial feed + 50 g TMB), P3 (commercial feed + 100 g TMB), P4 (commercial feed + 150 g TMB), and P5 (commercial feed + 200 g TMB). . Parameters observed in this study were absolute length growth, absolute weight growth, daily growth rate, amount of feed consumption, feed efficiency, survival rate and water quality (DO, pH and temperature). Based on the analysis of the Kruskall Wallis test, the dose of addition of mangrove mollusk flour had no significant effect (P>0.05) on all observation parameters. Meanwhile, data on water quality is still in need of catfish seeds.